1) 3(2n + 5) = 2n-8
Answers
Answered by
1
Simplifying
5n + -3 = 2n + -8
Reorder the terms:
-3 + 5n = 2n + -8
Reorder the terms:
-3 + 5n = -8 + 2n
Solving
-3 + 5n = -8 + 2n
Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right.
Add '-2n' to each side of the equation. -
3 + 5n + -2n = -8 + 2n + -2n
Combine like terms:
5n + -2n = 3n -3 + 3n = -8 + 2n + -2n
Combine like terms:
2n + -2n = 0 -3 + 3n = -8 + 0 -3 + 3n = -8
Add '3' to each side of the equation. -3 + 3 + 3n = -8 + 3 Combine like terms:
-3 + 3 = 0 0 + 3n = -8 + 3
3n = -8 + 3
Combine like terms:
-8 + 3 = -5 3n = -5
Divide each side by '3'. n = -1.666666667
Simplifying n = -1.666666667
Similar questions
Science,
3 hours ago
Political Science,
3 hours ago
Social Sciences,
6 hours ago
English,
8 months ago
English,
8 months ago